2014
DOI: 10.1007/s12185-014-1568-0
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory network governing Gata1 and Gata2 gene transcription orchestrates erythroid lineage differentiation

Abstract: GATA transcription factor family members GATA1 and GATA2 play crucial roles in the regulation of lineage-restricted genes during erythroid differentiation. GATA1 is indispensable for survival and terminal differentiation of erythroid, megakaryocytic and eosinophilic progenitors, whereas GATA2 regulates proliferation and maintenance of hematopoietic stem and progenitor cells. Expression levels of GATA1 and GATA2 are primarily regulated at the transcriptional level through auto-and reciprocal regulatory networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 56 publications
(93 reference statements)
1
49
0
Order By: Relevance
“…These two transcription factors display reciprocal expression profiles during erythropoiesis and play different roles in erythroid development: GATA-2 regulates proliferation and maintenance of erythroid and hematopoietic progenitors, while GATA-1 promotes differentiation (Bresnick et al, 2012; Fujiwara et al, 2004; Moriguchi and Yamamoto, 2014; Tsai et al, 1994). GATA-2 is a transactivator of Gata-1 during erythroid progenitor expansion (Bresnick et al, 2012; Cantor, 2005; Ferreira et al, 2005).…”
Section: Regulation Of Erythroid Developmentmentioning
confidence: 99%
“…These two transcription factors display reciprocal expression profiles during erythropoiesis and play different roles in erythroid development: GATA-2 regulates proliferation and maintenance of erythroid and hematopoietic progenitors, while GATA-1 promotes differentiation (Bresnick et al, 2012; Fujiwara et al, 2004; Moriguchi and Yamamoto, 2014; Tsai et al, 1994). GATA-2 is a transactivator of Gata-1 during erythroid progenitor expansion (Bresnick et al, 2012; Cantor, 2005; Ferreira et al, 2005).…”
Section: Regulation Of Erythroid Developmentmentioning
confidence: 99%
“…During erythroid differentiation, GATA-2 levels concomitantly decrease with increased GATA-1 levels (Bresnick et al 2010). Based on a murine model of erythroid differentiation, GATA-1 represses GATA-2 transcription by displacing GATA-2 from sites at −77, −3.9, −2.8, −1.8, and +9.5 kb relative to the 1S promoter, each of which is considered as "GATA switch site" (Bresnick et al 2010;Moriguchi et al 2014). Among these enhancers, deletion of the +9.5 site involving GATAbinding motif leads to delayed embryonic lethality compared with global Gata2 knockout (Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ATA1 is a member of the GATA zinc finger transcription factor family and plays a central role in erythropoiesis (1)(2)(3). GATA1 expression starts at common myeloid progenitor (CMP) stage, and the expression level increases when erythroid lineage cells differentiate into the proerythroblast stage (4,5).…”
mentioning
confidence: 99%
“…This dynamic change in GATA1 expression is essential for erythropoiesis, since constitutive expression of GATA1 at a high level under the regulation of the human ␤-globin gene in transgenic mice is lethal due to defective erythroid cell maturation (6). A series of studies have revealed that the Gata1 gene is regulated through the activity of multiple cisregulatory elements (1)(2)(3). However, the precise contribution of each cis-element to Gata1 expression in specific hematopoietic lineages and differentiation stages has not been fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation